2009
DOI: 10.1103/physrevd.80.085014
|View full text |Cite
|
Sign up to set email alerts
|

Solutions of coupled BPS equations for two-family Calogero and matrix models

Abstract: We consider a large N, two-family Calogero and matrix model in the Hamiltonian, collective-field approach. The Bogomol'nyi limit appears and the solutions to the coupled Bogomol'nyi-PrasadSommerfeld equations are given by the static soliton configurations. We find all solutions close to constant and construct exact one-parameter solutions in the strong-weak dual case. Full classification of these solutions is presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…All this was the consequence of the invariance of the collective-field Hamiltonian of the twofamily Calogero model under an Abelian group of strong-weak-coupling dualities [8], analogous to (1.7). In [24] and [25] it was shown that a large class of solitons in the two-family Calogero model can be obtained by reducing it to the effectively one-family Calogero model.…”
Section: Introductionmentioning
confidence: 99%
“…All this was the consequence of the invariance of the collective-field Hamiltonian of the twofamily Calogero model under an Abelian group of strong-weak-coupling dualities [8], analogous to (1.7). In [24] and [25] it was shown that a large class of solitons in the two-family Calogero model can be obtained by reducing it to the effectively one-family Calogero model.…”
Section: Introductionmentioning
confidence: 99%